Design of a novel concentrating photovoltaic–thermoelectric system incorporated with phase change materials. (15th March 2016) - Cui, Tengfei; Xuan, Yimin; Li, Qiang
Highlights: A novel photovoltaic–thermoelectric system integrated with phase change materials is proposed. The theoretical model of the PV–PCM–TE system is established to study its feasibility. The PV–PCM–TE system is proved to be superior to single PV cells and PV–TE systems. The influence parameters of the PV–PCM–TE system are investigated. Abstract: Since the solar irradiance within a day is varying, the temperature of the photovoltaic–thermoelectric (PV–TE) system becomes fluctuant with the change of the incident solar irradiance, which exerts a significant influence on the efficiency of the total system. In this paper, the phase change material (PCM) is introduced into the PV–TE system to construct a novel PV–PCM–TE hybrid system. The purposes of applying PCM are to mitigate the temperature fluctuations of the PV cell and the TE modules and keep the hybrid PV–TE system operating under a fixed operating condition. A theoretical model of evaluating the efficiency of the concentrating PV–PCM–TE hybrid system is presented. The feasibility of the PV–PCM–TE system with four types of PV cells, c-Si, CIGS, single-junction GaAs, and GaInP/InGaAs/Ge (III–V), are investigated. The optimum operating conditions which indicate that the PV–PCM–TE system has the highest total efficiency are discussed to determine the melting temperatures of PCMs. A series of structure parameters are designed to obtain the optimized parameters for the PV–PCM–TE system, and the influences of these parameters on the PV–PCM–TE system are investigated. The results indicate that the performance of the PV–PCM–TE system is superior to single PV cells and/or PV–TE systems.